Analisis Risiko Kerja Dan Upaya Pengendalian Bahaya Pada Petugas Pemadam Kebakaran Di Dinas Pemadam Kebakaran Kota Semarang - Aini, Alfi Nur (Jurnal Kesehatan Masyarakat (Undip), 2016)
Semarang city has a relatively rapid development, making it the hub of government activities, the center of industrial activity, trade, transportation, and educational activity center, the center of tourist activities as well as socio-cultural activity centers. Fire event was also developed along with the development of Semarang. Firefighters as the party that plays an important role in firefighting has a high occupational risks. The purpose of this study was to analyze the risks of work that can be known efforts to control hazards at firefighters in Semarang City Fire Department. This research is a qualitative descriptive approach. The research sample consisted of firefighters Fire Department Semarang related to outage activities as many as 11 people. The survey results revealed danger as occupational risks experienced firefighters are physical hazards, chemical hazards, and electrical hazards, dangers of mechanical, biological hazards and danger of height. Efforts for control of the risks of existing work includes the provision of Personal Protective Equipment (PPE), the shift rotation system in each platoon, providing training to broaden firefighters. Occupational risks faced by firefighters control varied and require a structured and comprehensive manner in order to prevent accidents when firefighters do fire fighting efforts at the fire location.